Hydrochemical analysis of groundwater from Brazilian aquifers by TXRF analysis - Bonotto, Daniel Marcos [UNESP]; Roveratti, Gabrielle (My University, 2017)
The Total X-rays Reflection Fluorescence principle (TXRF) has been widely used for water analysis, in which an X-ray monochromatic beam is reflected in a monochromator with multiples layers focused in the samples in a very small angle (<0.1°), causing its total reflection. The equipment developed for using it analyzes elements from Al to U in waters, other liquids, particulate and suspension material, metals, tissues and filters. One machine was installed at LARIN (Ionizing Radiation Laboratory), located in UNESPetro (Geosciences Center Applied to Petroleum), IGCE/UNESP, Rio Claro (SP), Brazil, with financial support from Petrobras company. In this chapter, we report the initial tests held to utilize the equipment for water analysis, as well its application in reporting hydrochemical data of Brazilian aquifers situated in São Paulo, Minas Gerais and Mato Grosso do Sul states. Samples of tap, deionized, Milli-Q and waste waters provided the first inputs for employing the equipment to run the groundwater analyzes. Then, water samples of nonconfined (codes SPO, AVR, ASB) and confined (codes PPA, PPE and PEO) zones from GAS (Guarani Aquifer System) in São Paulo State were analyzed. They were prepared on pipetting, in a container, 0.5 or 1 mL of the sample, adding 5 μL of the internal standard (ytrium, concentration = 1g/L), and agitating the solution. Then, a 5 μL-aliquot was deposited in a quartz disc that was heated up to ~60°C for 5 minutes. The concentration range, in mg/L, was: K = 0.082-0.508; Ca = 0.445-5.602; Fe = 0.005- 1.838; Zn = 0.002-0.029; Br = 0.016-0.020; Pb = 0.008-0.094; P = 1.738- 2.459; Sr = 0.003-0.055; Ti = 0.007-0.073; Ba = 0.31-0.226; Cr = 0.004- 0.094. In some samples, it was found Mn = 0.132 mg/L, Te = 0.199 mg/L, Ni = 0.004 mg/L and As = 0.005. The results obtained were coherent with the GAS characteristics, as evidenced by the presence of bromine (Br) in the aquifer confined zones. In view of them, the technique was utilized in different aquifer systems exploited for mineral waters and water-supply systems in the states of São Paulo, Minas Gerais and Mato Grosso do Sul. The trace metals found in the groundwater samples showed a great applicability in hydrogeochemical studies. It is a non-destructive method that is very clean, requiring neither sophisticated steps for sample preparation nor large amounts of reagents, among other advantages.